2011
DOI: 10.4028/www.scientific.net/amr.356-360.1570
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Waste Cutting Oil Emulsions by Leaching Solutions of White Mud

Abstract: A leaching solution of white mud was prepared from this waste material of soda production, and used for treatment of waste cutting oil emulsion. In alkaline conditions, the leaching solution of white mud generates hydroxide precipitates, which have relatively high specific surface area and excess surface energy, and readily adsorb the pollutants in waste cutting oil emulsion. The chemical composition of the white mud was determined and the hydroxide precipitates were characterized. The maximum removal efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, research was also conducted on the removal of oil-containing organic compounds, such as emulsified oil, 30 oil emulsions, 46 and petroleum sulfonate 31 from wastewater, with promising adsorption results ( Table 2 ). Studies have shown that soda residue and hydroxide particles formed in highly alkaline conditions restrict oil droplet migration via electrostatic attraction, hydrogen bonding, and particle surface adhesion, leading to the adsorption and encapsulation of oil droplets or organic components in the hydroxide crystals to effectively remove organic pollutants.…”
Section: Soda Residue Application For Environmental Protectionmentioning
confidence: 99%
“…Furthermore, research was also conducted on the removal of oil-containing organic compounds, such as emulsified oil, 30 oil emulsions, 46 and petroleum sulfonate 31 from wastewater, with promising adsorption results ( Table 2 ). Studies have shown that soda residue and hydroxide particles formed in highly alkaline conditions restrict oil droplet migration via electrostatic attraction, hydrogen bonding, and particle surface adhesion, leading to the adsorption and encapsulation of oil droplets or organic components in the hydroxide crystals to effectively remove organic pollutants.…”
Section: Soda Residue Application For Environmental Protectionmentioning
confidence: 99%